The Role of Higher Legal Education in Improving the Professional Capacity of Legislative Drafters Through the Legislative Drafting Class - Sihombing, Eka N. A. M. (Lembaga Riset Mutiara Akbar, 2024)
Legal higher education has a very important role in improving the capacity of human resources in the legal field, one of which is through teaching legislative drafting courses. This course is designed to equip students with skills in compiling and designing clear, precise, and legal regulations in accordance with legal principles. Quality regulatory drafters are needed to create effective and optimally implemented regulations. This study aims to explore how legal higher education, especially through legislative drafting courses, can strengthen students' abilities in designing quality laws and regulations. With a qualitative approach, this study examines the teaching materials taught, the teaching methods used, and the contribution of the course to improving the capacity of legal drafters. The results of the study show that teaching legislative drafting in universities not only provides technical skills, but also strengthens students' understanding of the legal principles underlying the creation of regulations. Therefore, legal higher education through this course has a significant contribution to improving the capacity of quality legal drafters and regulations in Indonesia.